Esperienza estetica e unità di coscienza (Itinera, 2013)
Jung considers the symbol as a unifying and transcendent element, as an image capable of unifying the various aspects of consciousness (sensation, intuition, feeling and thought) in a gradual rapprochement to the essential unity of being. However, this point is controversial,  since the symbol is the expression of a sense that while not entirely rational, concern the cognitive sphere. Therefore what Jung attributes to the symbol (its unifying and transcendent power) was transferred to the aesthetic experience of art, where the same aspects of consciousness in the symbol are supported by perceptual elements, according to a level of completeness and unity that only the aesthetic experience of art can achieve.